De santos e viagens: a construção comparada do conceito de santidade nas biografias de São Columba e São Columbanus - Boulhosa, Tatiana Machado (2009)
The aim of this dissertation is to discuss comparatively the construction of the concept of sainthood based on two distinct works: The Life of St Columba, written by Adomnán, abbot of Iona, in the last decades of the 7th century and The Life of St Columban, written by Jonas of Bobbio, in the mid-7th century. In both cases it is the pursuit of the image of sainthood that gives the narrative its primary sense; therefore they can and in fact are referred to as hagiographies. However, their history cannot be fully understood if the wider context is not first comprehended. Therefore, this dissertation opens up with a sketch of the surrounding events that made them possible, that is to say, Celtic Christianity. We also aim to point out the various interpretations surrounding the phenomenon and its implications in the final shaping of a theoretical model of Medieval monastic Saints: illuminated men, withdrawn from society, capable of articulating under their wings a great number of followers, whose power flowed from their example and illustration. Such people represent part of the Medieval Imaginary, articulators of its mentality, translators in deeds as well as in words of the ways in which Medieval Society saw the world: an eternal struggle to be worthy of God´s love. Entwined both with History and Sociology, such model becomes part of the Religious Studies and ends up guiding the reading of the mentioned hagiographies, helping us understand the role these monks played during the first centuries of Christianity, not only as spiritual but also as political leaders